Pozaliturgiczna aktywność świeckich chrześcijan w Egipcie podczas eucharystii między IV a XV w. n.e. - Piwowarczyk, Przemysław; Nieuważny, Adam (Vox Patrum, 2025)
The article documents non-liturgical forms of lay Christian activities during the Eucharist in Egypt between the 4th and 15th centuries and provides context for them. This is the first comprehensive attempt of this kind in research on Egyptian Christianity. The study takes into account the liturgical, linguistic, and spatial conditions of the Egyptian mass. It is based on scattered references in various sources in Greek, Coptic, and Arabic (including some Ethiopian and Syriac sources). These sources are of a legal-canonical, homiletic, hagiographic, and encyclopedic nature. An integral part of the article is a selection of sources translated into Polish. The analyses suggest that the Eucharistic liturgy was not only a religious event but also a significant social occasion. In addition to the official celebration, the church was also a place for parallel private devotion. Many of the faithful were excluded from full participation in the liturgy due to the church's spatial organization and the incomprehensible language.